Answer:
In the interval of - 2 ≤ t ≤ 4, the average rate of change is zero.
Step-by-step explanation:
The function is given to be ............ (1)
(i) Now, for 1 ≤ t ≤ 4, we will put t = 1 and t = 4.
So, g(1) = 5, g(4) = - 4. {From equation (1)}
Hence, g(1) ≠ g(4)
(ii) Now, for - 4 ≤ t ≤ - 3, we will put t = - 4 and t = - 3.
So, g(- 4) = - 20, g(- 3) = - 11. {From equation (1)}
Hence, g(- 4) ≠ g(- 3)
(iii) Now, for -2 ≤ t ≤ 0, we will put t = - 2 and t = 0.
So, g(- 2) = - 4, g(0) = 4. {From equation (1)}
Hence, g(- 2) ≠ g(0)
(iv) Now, for - 2 ≤ t ≤ 4, we will put t = - 2 and t = 4.
So, g(- 2) = - 4, g(4) = - 4. {From equation (1)}
Hence, g(- 2) = g(4)
Therefore, in the interval of - 2 ≤ t ≤ 4, the average rate of change is zero. (Answer)
Answer:
Width = 5 and Length = 9 units.
Step-by-step explanation:
Let the width be W, then the length L = 3W - 6.
Perimeter = 2W + 2L = 2W + 2(3W - 6) = 28.
2W + 6W - 12 = 28
8W = 40
W = 5 units.
Therefore L = 3(5) - 6 = 9 units.
Step-by-step explanation:
Length:
l = 3w - 6
Perimeter:
P = 2l + 2w = 2(3w - 6) + 2w = 8w - 12 = 28 --> w = 5
l = 3*5 - 6 = 9